Lifestyle medicine applied to late complications of diabetes mellitus. Case report: Medicina de Estilos de Vida aplicado a complicaciones tardías de la Diabetes Mellitus. Reporte de caso - Castillo Velarde, Edwin (2021)
Diabetes mellitus is the main cause of progression of chronic kidney disease and dialysis. The therapeutic intervention considers an HbA1C level that avoids adverse effects associated with hypoglycemic therapy, as occurs in patients with chronic kidney disease, despite not reaching normoglycemia. The present case describes an intervention based on Lifestyle Medicine in a patient with diabetic nephropathy and chronic kidney disease, whose biomarkers showed improvement in kidney damage due to reduction of proteinuria or reduction of HbA1C, LDL and triglycerides in its metabolic control. The intervention with lifestyle medicine requires a multidisciplinary approach and the time of intervention does not discriminate a degree of chronic kidney disease that limits its intervention